Sensitivity Study of Dynamic Response and Seismic Performance of Offshore Tripod Structure Under Variation of Center of Gravity Location - Novan Arif Hidayat; Daniel Mohammad Rosyid; Yoyok Setyo Hadiwidodo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
An effective weight control is critical for managing gravity loads and the center of gravity (CoG) evolution in offshore platforms. International standards, including ISO 19901-5:2021, require that CoG shift envelopes—defined in 2D (X–Y) and 3D (X–Y–Z) coordinate systems—be considered when assessing pile foundation capacity and global structural behavior. This study examines the sensitivity of the dynamic response and seismic performance of a three-legged fixed offshore structure (tripod) due to variation of CoG location. Tripod known have characteristic as slender structure and long natural period that make it particularly sensitive to gravity loads, lateral forces, and soil variability. A systematic sensitivity analysis was performed using 75 cases, spanning four directional quadrants in both 2D and 3D (upward and downward) associated with 0%, 10%, and 20% of topside operating mass increment. Dynamic and in-place analyses incorporating pile-soil interaction (PSI) were conducted using SACS software. Seismic performance was evaluated through response spectrum–based equivalent static methods. The results show variation of CoG location influenced the dynamic response and structural performance. The response determined significantly amplify if the CoG variation associated with mass increment, particularly under in-place conditions that exhibited greater sensitivity than seismic condition. The study also proposes a CoG shift envelope that maintains acceptable structural performance and recommends its adoption in future design and modification planning. Emphasis is placed on active CoG management and the necessity for future non-linear assessments to capture post-elastic behavior and ensure the robustness of tripod platform design.